ANALISIS KINERJA REKSADANA SAHAM - Hermeindito Kaaro (Journal of Management and Business, 2007)
The issue of Indonesian mutual fund crisis in 2005 has not been resolved satisfactorily. Many investors may reluctant to invest in mutual fund market due to the lack of knowledge about the risk and return. Most mutual fund investors are quasi-investors who shift their assets class from less risky asset to risky assets. Hence, this study attempts to resolve the problem, especially in evaluating and analyzing mutual fund performance in Indonesia. The purposes of this study are a) to investigate whether mutual fund outperforms particular benchmarks (market return and risk free rate); b) to analyze both consistency and persistency of mutual fund performance. Sample of this study are 15 equity mutual funds, which provides data from January 2004 to December 2006. Jensen’s Alpha, Treynor and Sharpe indexes are used in this study to measure fund performance. Market adjusted models are used in measuring abnormal return. The t-test is used to test fund performance. This study employs coefficient concordance Kendall’s W to measure the consistency of fund performance. While, autoregressive distribution lag models are employed to analyze the persistency of fund performance. This study finds that fund performance outperforms the particular benchmarks significantly. This study also provides evidence, which supports the hypothesis that there are consistency and persistency of fund performances phenomena in Indonesia. The research results suggest investor’s redemption in mutual fund market in 2005 may not caused by worse fund performance or both inconsistence nor persistence in mutual fund performance, rather than it may caused by investor’s mental set and their lack of knowledge about risk and return.